2021
DOI: 10.3390/brainsci11020148
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Sex-Based Differences in Plasma Autoantibodies to Central Nervous System Proteins in Gulf War Veterans versus Healthy and Symptomatic Controls

Abstract: Veterans from the 1991 Gulf War (GW) have suffered from Gulf War illness (GWI) for nearly 30 years. This illness encompasses multiple body systems, including the central nervous system (CNS). Diagnosis and treatment of GWI is difficult because there has not been an objective diagnostic biomarker. Recently, we reported on a newly developed blood biomarker that discriminates GWI from GW healthy controls, and symptomatic controls with irritable bowel syndrome (IBS) and myalgic encephalomyelitis/chronic fatigue sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“… 3 Numerous objective markers have been found to be altered in GWI, 4 , 5 , 6 , 7 though there is no pathognomonic test. Alterations with replicated documentation include increased inflammation, 8 , 9 mitochondrial impairment, 6 , 10 , 11 , 12 altered eicosanoids, 4 altered hormone status, 13 , 14 altered autonomic function, 7 , 15 , 16 and increased autoantibodies 5 , 17 , 18 —among others.…”
Section: Introductionmentioning
confidence: 99%
“… 3 Numerous objective markers have been found to be altered in GWI, 4 , 5 , 6 , 7 though there is no pathognomonic test. Alterations with replicated documentation include increased inflammation, 8 , 9 mitochondrial impairment, 6 , 10 , 11 , 12 altered eicosanoids, 4 altered hormone status, 13 , 14 altered autonomic function, 7 , 15 , 16 and increased autoantibodies 5 , 17 , 18 —among others.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of a chronic inflammatory response has been reported in studies on GW veteran cohorts, where blood samples are taken and analyzed for biomarkers of inflammation. These studies have reported dysregulation of immune cells and other inflammatory markers such as C-reactive protein, Tau proteins, complement proteins, cytokines and chemokines [13,[65][66][67]. This may in part explain why patients with GWI report multiorgan disorders whose causes are difficult to pinpoint.…”
Section: Discussionmentioning
confidence: 99%
“…Potential objective biomarkers of GWI were identified based on blood-based central nervous system autoantibodies [ 12 ]. In addition, sex differences in CNS autoantibodies were identified in the second issue, suggesting that men and women veterans may benefit from different therapeutic strategies [ 13 ]. Finally, the following were introduced to the field with samples and data freely available to GWI researchers: a much-needed brain tissue biorepository [ 14 ], and a biorepository of existing and newly obtained biospecimens, brain imaging, and corresponding demographics, health symptom surveys and neurotoxicant exposure histories [ 15 ].…”
mentioning
confidence: 99%